Synthesis of Nd2O3/SiO2 Material Applying for the Growth of Paramignya trimera - Nhan, Le Thi Hong; Lieu, Nguyen Thi; Hoa, Vo Thi Trong; Khue, Ngo Kim; Dieu, Phan Thi; Quóc, Nguyen Tri; Mai, Vo Thi Tuyet; Doc, Nguyen Dinh; Thuy, Do Thi Diem; Hoang, Cao Van (VNU Journal of Science: Natural Sciences and Technology, 2024)
This study focused on synthesis of Nd 2 O 3 /SiO 2 material and its applications as plant stimulant for Paramignya trimera (Oliv.) Guill. (Rutaceae) . A solid-phase heating method was used to successfully synthesize Nd 2 O 3 /SiO 2 material from Nd(NO 3 ) 3 and SiO 2 precursors. The cultivation results indicated the potential application of the synthesized Nd 2 O 3 /SiO 2 material as plant stimulants to induce root growth of Paramignya trimera as compared to the control, SiO 2 and Nd 2 O 3 exposed plants. Root length of the control, SiO 2 , Nd 2 O 3 and Nd 2 O 3 /SiO 2 exposed Paramignya trimera were 12.11, 15.12, 17.56 và 26.12 cm, respectively. Silica is a nutrient that promotes growth, increases crop output by assisting in the formation and regeneration of plant cell walls. Nd 2 O 3 increased the seedling and root growth. Combining both SiO 2 and Nd 2 O 3 exhibited synergic effects to greatly induce root growth of the Paramignya trimera . The root length of the Nd 2 O 3 /SiO 2 material exposed plant were greatly higher than those of the individual material exposed plants.